Queering Comradeship: Anti-Capitalist Relations in We Are Who We Are - David Reznik (Kvinder, Køn & Forskning, 2022)
Queering Comradeship: Anti-Capitalist Relations in We Are Who We Are. This article argues that We Are Who We Are’s value lies in its exploration of the radical relationality of comradeship, a concept theorized recently by Jodi Dean. The profoundly queer connection forged and cultivated by the show’s dual protagonists, Caitlyn/Harper Poythress and Fraser Wilson, inspiringly models a comradeship that overflows with everyday possibilities for contemporary anti-capitalist praxis. The article begins by tracing the outlines of the material landscape in which Fraser and Caitlyn/Harper’s relationship unfolds, namely an American military base which captures the contradictory dynamics of our contemporary social totality. The queer theory of Jasbir Puar is also used to highlight the intersections of gender/sexuality, imperialism, and political economy. The article then offers a close reading of the show, using Dean’s (2019) four theses of the comrade as an organizing structure. Special attention is paid to the relational dynamics between Caitlyn/Harper and Fraser, juxtaposing them with those of others in their immediate lives. The article concludes by using recent sociological research on youth activism to argue that the political legacy left by Fraser and Caitlyn/Harper can, in fact, inspire revolutionary change and promote the everyday subversion of global war capital.